Cytokine Response in SARS-CoV-2 Infection in the Elderly - Sherwani, Subuhi (J Inflamm Res, 2020)
The last few months of 2019 witnessed the emergence, rise and rapid spread of a novel coronavirus known as severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2), causing an acute respiratory disease called coronavirus disease 2019 or Covid-19. Severe pathological manifestations of the disease in the infected population with comorbidities are linked to acute respiratory distress syndrome (ARDS), associated with an exaggerated synthesis and expression of cytokines, leading to a systemic inflammatory response also known as a cytokine storm (CS). Elderly patients (>60 years of age) showed more deaths in Covid-19 infection. Age-related immune imbalance increases patient susceptibility to CS. In acute Covid-19 infection, it is difficult to minimize or control the overproduction of cytokines; hence, limited medical treatments are effective. This review aims to provide an overview of the current knowledge of involvement of cytokines in SARS-CoV-2 infection, susceptibility factors for the accompanying cytokine storm in severe Covid-19 cases and possible treatment strategies.